Odor hedonic responses in children and young people with profound intellectual and multiple disabilities - De Blasio, Catherine; Dind, Juliane; Petitpierre, Geneviève (Frontiers in Psychiatry, 2023)
Introduction Odors are closely linked to emotions, play an important role in the well-being of individuals and can influence mood. Despite these crucial properties, the hedonic responses to odors of people with profound intellectual and multiple disabilities (PIMD) remain little explored. Aim This within-subjects study aims to examine whether children and young people with PIMD react in a differentiated way to odors evaluated as pleasant or unpleasant by neurotypical adults and, if so, with which behaviors. The influence of their global mood on their emotional responses to odors is also examined. Method Twenty children and young people (7–18 years old) with PIMD were exposed to four pairs of hedonically contrasted odors. A control stimulus was presented before each odorant. Five emotional responses, one physiological reaction (nausea reactions), and three responses reflecting approach toward or avoidance of the stimulus were recorded throughout the duration of the stimulus exposure. The participants’ global mood status was measured before the start of the research with the French version of the Mood, Interest and Pleasure Questionnaire (Ross and Oliver, 2003). Results The results show that when exposed to pleasant odorants, participants kept their heads aligned with the odorant source longer, smiled longer, and produced more positive vocalizations. In contrast, unpleasant odorants elicit more pouts and grimaces. Nausea reactions occurred in the presence of unpleasant odorants. The hedonic responses were more marked during the second presentation of the stimuli. Participants with a higher MIPQ score showed significantly more emotional reactions to odors. Conclusion The results confirm the presence of olfactory preferences in participants with PIMD and the existence of a link between their mood, emotions and olfactory hedonic processing. They prompt the use of odors to support not only the cognitive development of this population, but also their mood and their emotional regulation abilities.